Field study on jet grouting columns performance above and below groundwater table in sandy soil - Mohsen Sabermahani; Amir Hajisalimi (Case Studies in Construction Materials)
The presence of the groundwater table within the jet grouting column execution zone frequently occurs in many projects, influencing column performance. Soil saturation plays a crucial role in these conditions, yet it has received limited attention in previous studies. In this study, 11 full-scale jet grouting columns were executed using a single-fluid system at a sandy site near the Caspian Sea in northern Iran to compare column diameter, treatment efficiency, and uniaxial compressive strength (UCS) above and below the groundwater. By altering injection pressure and rod lifting speed, different jet energy levels were applied to create the columns. The results indicated that maximum column diameter and treatment efficiency were observed in fully saturated sand, with an average 28 % increase in diameter compared to columns in partially saturated sand (Sr=50 %). Given the significant effect of jet energy on diameter at varying saturation levels, a practical equation along with iso-diameter curves was proposed to estimate the column diameter in single-fluid jet grouting in sand based on these two parameters. Additionally, the empirical equation by Flora et al. was modified to account for a 20 % discrepancy observed in the measured diameters in partially saturated sand. At all saturation levels, increased jet energy due to higher injection pressure improved volumetric efficiency, whereas a reduction in rod lifting speed had the opposite effect. UCS tests on core samples extracted from the columns revealed that core strength was 47 % higher in partially saturated sand (Sr=50 %) than in fully saturated sand.